Ischemic Vascular Damage Can Be Repaired by Healthy, but Not Diabetic, Endothelial Progenitor Cells - Caballero, Sergio; Sengupta, Nilanjana; Afzal, Aqeela; Chang, Kyung-Hee; Li Calzi, Sergio; Guberski, Dennis L.; Kern, Timothy S.; Grant, Maria B. (Diabetes (New York, N.Y.), 2007)
Ischemic Vascular Damage Can Be Repaired by Healthy, but Not Diabetic, Endothelial Progenitor Cells Sergio Caballero 1 , Nilanjana Sengupta 1 , Aqeela Afzal 1 , Kyung-Hee Chang 1 , Sergio Li Calzi 1 , Dennis L. Guberski 2 , Timothy S. Kern 3 and Maria B. Grant 1 1 Program in Stem Cell Biology, Department of Pharmacology and Therapeutics, University of Florida, Gainesville, Florida 2 Biomedical Research Models, Worcester, Massachusetts 3 Department of Medicine, Case Western Reserve University, Cleveland, Ohio Address correspondence and reprint requests to Maria B. Grant, MD, Pharmacology and Therapeutics, University of Florida, P.O. Box 100267, Gainesville, FL 32610-0267. E-mail: grantmaatpharmacology.ufl.edu Abstract Endothelial precursor cells (EPCs) play a key role in vascular repair and maintenance, and their function is impeded in diabetes. We previously demonstrated that EPCs isolated from diabetic patients have a profound inability to migrate in vitro. We asked whether EPCs from normal individuals are better able to repopulate degenerate (acellular) retinal capillaries in chronic (diabetes) and acute (ischemia/reperfusion [I/R] injury and neonatal oxygen-induced retinopathy [OIR]) animal models of ocular vascular damage. Streptozotocin-induced diabetic mice, spontaneously diabetic BBZDR/Wor rats, adult mice with I/R injury, or neonatal mice with OIR were injected within the vitreous or the systemic circulation with fluorescently labeled CD34 + cells from either diabetic patients or age- and sex-matched healthy control subjects. At specific times after administering the cells, the degree of vascular repair of the acellular capillaries was evaluated immunohistologically and quantitated. In all four models, healthy human (hu)CD34 + cells attached and assimilated into vasculature, whereas cells from diabetic donors uniformly were unable to integrate into damaged vasculature. These studies demonstrate that healthy huCD34 + cells can effectively repair injured retina and that there is defective repair of vasculature in patients with diabetes. Defective EPCs may be amenable to pharmacological manipulation and restoration of the cells’ natural robust reparative function. EPC, endothelial precursor cell I/R, ischemia/reperfusion LSCM, laser scanning confocal microscope OIR, oxygen-induced retinopathy SDF, stromal-derived factor STZ, streptozotocin VEGF, vascular endothelial growth factor Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted December 25, 2006. Received September 6, 2006. DIABETES